The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fendo.2023.1191935
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity and sitting with metabolic syndrome and hyperglycemic clamp parameters in adolescents – BRAMS pediatric study

Abstract: IntroductionObesity and metabolic syndrome (MetS) have immediate and long-term consequences on adolescent health and well-being. Among the available treatments for MetS in adolescents, behavioral interventions such as increasing physical activity (PA) are preferred. This study aimed to investigate the association of PA and sitting time with MetS and a complete set of metabolic health parameters.MethodsData from the Pediatric Brazilian Metabolic Syndrome Study (BRAMS-P), a cross-sectional multicenter study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Longer-term BP monitoring and experimental research are needed to explore the association between sitting time and BP. A weak unfavourable association between sitting time and insulin have been found in this study and similar to the finding among adults [47], however this association has not been found among adolescents [48]. The unexpected association with LDL observed in our study warrants careful consideration.…”
Section: Discussionsupporting
confidence: 83%
“…Longer-term BP monitoring and experimental research are needed to explore the association between sitting time and BP. A weak unfavourable association between sitting time and insulin have been found in this study and similar to the finding among adults [47], however this association has not been found among adolescents [48]. The unexpected association with LDL observed in our study warrants careful consideration.…”
Section: Discussionsupporting
confidence: 83%
“…From ten journal articles analyzed, important findings were revealed regarding the relationship between physical activity, metabolic parameters, and cardiovascular risk factors. One of the main findings is from Silva et al (2023), who found that adolescents with more than 8 hours of sitting time have a higher chance of MetS, while those who engage in moderate-high physical activity show improved insulin sensitivity. This highlights the importance of physical activity in reducing metabolic health risks in adolescents.…”
Section: Resultsmentioning
confidence: 99%